Bahasa Inggris - Dellby, Chintya; Aam Slamet Rusydiana; Indra (Universitas Airlangga, 2024)
This study aims to investigate the factors that influence customer loyalty to halal restaurants in Indonesia. The study uses purposive sampling and quantitative analysis based on structural equation modeling (SEM) with partial least squares (PLS) to analyze the factors that determine customer loyalty. Data were collected through an online questionnaire completed by 148 customers of halal restaurants in Indonesia and analyzed using the SEM-PLS method. The research results indicate that brand image, halal certification, and religion are mediating variables that have a positive and significant influence on customer loyalty to halal restaurants in Indonesia. This study makes a significant theoretical contribution to the understanding of the determinants of customer loyalty by integrating different theoretical perspectives, thereby serving as a basis for practitioners and Relevant policymakers to direct the development of the halal industry, especially the halal food supply sector in Indonesia.